2020
DOI: 10.1111/add.14953
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine replacement therapy sampling for smoking cessation within primary care: results from a pragmatic cluster randomized clinical trial

Abstract: Background and Aims Within the context of busy clinical settings, health‐care providers need practical, evidence‐based options to engage smokers in quitting. Sampling of nicotine replacement therapy [i.e. provision of nicotine replacement therapy (NRT starter kits)] is a brief, pragmatic strategy to address this need. We aimed to compare the effects of NRT sampling plus standard care (SC), relative to SC alone, provided by primary care providers during routine clinic visits. Design Cluster‐randomized clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…First, particularly for trials in which there is some potential for study-related risks, adverse event monitoring is critical. Trials have begun to implement remote procedures for adverse event monitoring including via phone and automated electronic surveys, 21 but there is great potential to improve real-time adverse event monitoring and response to such events within the context of remote trials. Second, for tobacco-focused trials, innovating methods for real time, continuous, remote measurement of cotinine will improve the options for remote biochemical verification of tobacco use status and address limitations to current remote cotinine collection options.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, particularly for trials in which there is some potential for study-related risks, adverse event monitoring is critical. Trials have begun to implement remote procedures for adverse event monitoring including via phone and automated electronic surveys, 21 but there is great potential to improve real-time adverse event monitoring and response to such events within the context of remote trials. Second, for tobacco-focused trials, innovating methods for real time, continuous, remote measurement of cotinine will improve the options for remote biochemical verification of tobacco use status and address limitations to current remote cotinine collection options.…”
Section: Discussionmentioning
confidence: 99%
“…In our own prior studies that have utilized mailed consent procedures, return rates have been somewhat low, with nonresponse rates of approximately 45%–50%. 21 , 22 To improve upon this process, we are currently exploring the added utility of a $5 noncontingent incentive, mailed with consent forms in a similar manner as many paper-based household surveys are conducted. 23 , 24 Study recruitment is ongoing and early results should be interpreted with caution; nonetheless, among mailed consent forms sent to date (775 total), response rates to mailings with the $5 incentive versus not have been 45.5% versus 35%, which equates to a cost of $48.78 per additional participant enrolled.…”
Section: Remote Consentmentioning
confidence: 99%
“…In summary, this large randomized clinical trial examined medication sampling as a brief and disseminable treatment to promote smoking cessation in primary care. Patient outcomes of medication sampling were favorable [ 17 ], with an increase in medication uptake and cessation at six months. Analyses herein provide further support for medication sampling at the provider level: sampling is a useful tool that more effectively allows healthcare providers to concretely assist their patients with smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
“…We report herein on receipt of cessation advice from a recently completed cluster randomized clinical trial that evaluated the impact of medication sampling on patient outcomes. Both the study methods [ 16 ] and participant-based outcomes [ 17 ] are reported elsewhere. While medication sampling was hypothesized to promote smoking abstinence at the patient level (and resulted in 1.5-fold increase in cessation), it was secondarily hypothesized to increase compliance with brief advice guidelines, insofar that giving providers a concrete, immediately actionable tool to offer to their patients might facilitate a deeper and more impactful conversation about quitting.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the low‐burden practice of medication sampling (e.g. providing a 2‐week starter pack of nicotine replacement therapy) without intensive co‐occurring counseling has been shown to increase quit attempts and abstinence with little training required [18]. Although it is not harm reduction per se , medication sampling is an example of a pragmatic strategy that could catalyze cessation behavior, even among unmotivated smokers.…”
mentioning
confidence: 99%